Protective effect of Matricaria Chamomilla extract on hepatic-renal toxicity of ceftriaxone in rats - Farouk, Mona; Abokora, Seham; Ali, Abdel-Fatah (International Journal of Pharmacology and Toxicology, 2017)
The effect of Matricaria chamomilla (M.chamomilla) against hepatic-renal toxicity of Ceftriaxone was investigated in this study. Twenty eight rats were divided into four groups. The 1st group was injected with saline as control, the 2nd Â and 3rd Â groups were injected with M.chamomilla extraction ( 50mg/kg.b.wt) and with ceftriaxone ( 180 mg/kg.b.wt.) for two and one week respectively while the 4th Â group was injected with M.chamomilla extraction plus ceftriaxone. at dose 50mg/kg and 180 mg/kg.b.wt respectively ,daily for the one week and with M.chamomilla extraction only at dose 50mg/kg.b.wt for another week. At the end of the 1st Â week, the 3rd group had significantly higher ALP,ALT,AST, urea and creatinine levels with significantly lower albumin and A/G ratio levels than that of the 1st and 2nd groups , while the 4th Â group did not differ from 1st and 2nd groups in terms of these parameters. Histopathological studies revealed that, the 3rd Â group had some pathological changes in the liver and kidney.From this study we can conclude that, M. chamomilla extraction Â can reduce hepatic-renal toxicity of ceftriaxone in rats.